Intracellular Metabolism of the Nucleotide Prodrug GS-9131, a Potent Anti-Human Immunodeficiency Virus Agent - Ray, Adrian S. (American Society for Microbiology (ASM), 2008)
GS-9131 is a phosphonoamidate prodrug of the novel ribose-modified phosphonate nucleotide analog GS-9148 that demonstrates potent anti-human immunodeficiency virus type 1 (HIV-1) activity and an excellent resistance profile in vitro. Prodrug moieties were optimized for the efficient delivery of GS-9148 and its active diphosphate (DP) metabolite to lymphoid cells following oral administration. To understand the intracellular pharmacology of GS-9131, incubations were performed with various types of lymphoid cells in vitro. The intracellular accumulation and antiviral activity levels of GS-9148 were limited by its lack of cellular permeation, and GS-9131 increased the delivery of GS-9148-DP by 76- to 290-fold relative to that of GS-9148. GS-9131 activation was saturable at high extracellular concentrations, potentially due to a high-affinity promoiety cleavage step. Once inside the cells, GS-9148 was efficiently phosphorylated, forming similar amounts of anabolites in primary lymphoid cells. The levels of GS-9148-DP formed in peripheral blood mononuclear cells infected with HIV-1 were similar to that in uninfected PBMCs, and approximately equivalent intracellular concentrations of GS-9148-DP and tenofovir (TVF)-DP were required to inhibit viral replication by 90%. Once it was formed, GS-9148-DP was efficiently retained in activated CD4(+) cells, with a half-life of 19 h. In addition, GS-9131 showed a low potential for drug interactions with other adenine nucleoside/nucleotide reverse transcriptase inhibitors, based on the lack of competition for anabolism between suprapharmacologic concentrations of GS-9148 and TVF and the lack of activity of GS-9131 metabolites against purine nucleoside phosphorylase, an enzyme involved in the clearance of 2′,3′-dideoxyinosine. Together, these observations elucidate the cellular pharmacology of GS-9131 and illustrate its efficient loading of lymphoid cells, resulting in a prolonged intracellular exposure to the active metabolite GS-9148-DP.